Fabrication of a Hand-held Electronic Nose - Marni Azira, Markom; Ali Yeon, Md Shakaff; Abdul Hamid, Adom; Mohd Noor, Ahmad; Abu Hassan, Abdullah (Universiti Malaysia Perlis, 2009)
An electronic nose is a device that performs the electronic olfactory to substitute human experts. The development of these devices is growing faster due to higher demand. However, current electronic noses usually are very complicated and expensive. This paper presents the work of the fabrication of a handheld electronic nose for commercialisation. The fabrication of the electronic nose involved three stages: software, hardware and case development. The e-nose consists of a sensors array integrated with Hitachi microcontroller and neural network algorithm as pattern recognition. The completed enose showed that it was able to discriminate sample which infected by ganoderma spp.